Synthesis and Characterization of Nanotubes from Misfit (LnS)1+yTaS2 (Ln=Pr, Sm, Gd, Yb) Compounds. Issue 44 (26th July 2018) - Serra, Marco; Stolovas, Dalit; Houben, Lothar; Popovitz‐Biro, Ronit; Pinkas, Iddo; Kampmann, Felix; Maultzsch, Janina; Joselevich, Ernesto; Tenne, Reshef
Abstract: The synthesis and characterization of nanotubes from misfit layered compounds (MLCs) of the type (LnS)1+ y TaS2 (denoted here as LnS‐TaS2 ; Ln=Pr, Sm, Gd, and Yb), not reported before, are described (the bulk compound YbS‐LaS2 was not previously documented). Transmission electron microscopy and selected area electron diffraction showed that the interlayer spacing along the c axis decreased with an increase in the atomic number of the lanthanide atom, which suggested tighter interaction between the LnS layer and TaS2 for the late lanthanides. The Raman spectra of the tubules were studied and compared to those of the bulk MLC compounds. Similar to the bulk MLCs, the Raman spectra could be divided into the low‐frequency modes (110–150 cm −1 ) of the LnS lattice and the high‐frequency modes (250–400 cm −1 ) of the TaS2 lattice. The Raman spectra indicated that the vibrational lattice modes of the strained layers in the tubes were stiffer than those in the bulk compounds. Furthermore, the modes of the late lanthanides were higher in energy than those of the earlier lanthanides, which suggested larger charge transfer between the LnS and TaS2 layers for the late lanthanides. Polarized Raman measurements showed the expected binodal intensity profile (antenna effect). The intensity ratio of the Raman signal showed that the E2g mode of TaS2 was more sensitive to the light‐polarization effect than its A1g mode. These nanotubes are expected to reveal interesting low‐temperature quasi‐1D transport behavior. Abstract : A bunch of misfits : The synthesis and characterization of nanotubes from misfit layered compounds of the type (LnS)1+ y TaS2 (Ln=Pr, Sm, Gd, and Yb) are described. Transmission electron microscopy and selected area electron diffraction suggest tight interaction between the LnS layer and TaS2 for late lanthanides. These nanotubes are expected to reveal interesting low‐temperature quasi‐1D transport behavior.